2006
DOI: 10.1007/s10584-005-9011-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Assessment of Growing Stock, Biomass and Carbon Stock of Indian Forests

Abstract: The dynamics of terrestrial ecosystems depends on interactions between carbon, nutrient and hydrological cycles. Terrestrial ecosystems retain carbon in live biomass (aboveground and belowground), decomposing organic matter, and soil. Carbon is exchanged naturally between these systems and the atmosphere through photosynthesis, respiration, decomposition, and combustion. Human activities change carbon stock in these pools and exchanges between them and the atmosphere through land-use, land-use change, and fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…Studies have been summarized in Table 2. Manhas et al (2006) reported the India's total carbon stock as 1085.06 and 1083.69 Mt in 1984 and 1994, respectively. The major forests contributed to carbon stock were of the order of: Miscellaneous forest > Shorea robusta forest > Tectona grandis forest > Temperate forest > Tropical forest > Bamboo forest, etc.…”
Section: Indian Forest Ecosystem Biomass/carbon Estimatesmentioning
confidence: 99%
“…Studies have been summarized in Table 2. Manhas et al (2006) reported the India's total carbon stock as 1085.06 and 1083.69 Mt in 1984 and 1994, respectively. The major forests contributed to carbon stock were of the order of: Miscellaneous forest > Shorea robusta forest > Tectona grandis forest > Temperate forest > Tropical forest > Bamboo forest, etc.…”
Section: Indian Forest Ecosystem Biomass/carbon Estimatesmentioning
confidence: 99%
“…The most important driver of deforestation in north eastern parts of India is the practice of shifting cultivation 53 . Forests are owned mostly by communities in the north east India.…”
Section: Spatial Coverage Across Statesmentioning
confidence: 99%
“…Forests are owned mostly by communities in the north east India. In Nagaland 91% of forest land is under the control of communities, followed by 90% in Meghalaya, 68% in Manipur, 62% in Arunachal Pradesh, 41% in Tripura and 33% in Mizoram and Assam 53 . Shifting cultivation affected 10 m ha of forests in the north eastern parts of India 54 .…”
Section: Spatial Coverage Across Statesmentioning
confidence: 99%
“…Based on satellite image, Forest Survey of India estimates 1.73 million hectares of land as being affected by shifting cultivation. Decrease in forest area due to shifting cultivation is estimated to account for 23% of the total deforestation in India [11].…”
Section: Drivers Of Deforestationmentioning
confidence: 99%